Corpus-Based Approach to Sociolinguistic Study of Offensive Words: Gender, Time and Register Differences - Doung, Dara; Ny, Sun; Saleem, Muhammad (Journal of Language Development and Linguistics, 2023)
The unpleasant expressions (offensiveness) always emotionally affect to the human psyches, and exists in all languages in less or strong degrees and directly or indirectly. Therefore, this study aimed to investigate over the changes of them by corporally-derived data and their registers, times and genders were the pilot targets. BNC and COCA Corpora were put for data collections while the list of previous insulting words was selected to reuse, especially the ones with highest frequencies. The results suggested 4 words damn, shit, fuck and dick had the highest degrees of uses but those from BNC were comparatively fewer than the rest. Moreover, the top four were emerged up to the different periods of times and contexts while men used them considerably more often than the women did.